2007
DOI: 10.1109/twc.2007.348336
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Non-Regenerative MIMO Wireless Relays

Abstract: Abstract-Given a multiple-antenna source and a multipleantenna destination, a multiple-antenna relay between the source and the destination is desirable under useful circumstances. A non-regenerative multiple-antenna relay, also called nonregenerative MIMO (multi-input multi-output) relay, is designed to optimize the capacity between the source and the destination. Without a direct link between the source and the destination, the optimal canonical coordinates of the relay matrix are first established, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
623
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(647 citation statements)
references
References 17 publications
4
623
0
4
Order By: Relevance
“…We compare the performance of the proposed OPT-COV algorithm with the naive amplify-and-forward (NAF) algorithm [5], the pseudo match-and-forward (PMF) algorithm [5], SUB algorithm [9], the JMMSE-COV algorithm [15], OPT algorithm [9] and the suboptimal covariance (SUB-COV) algorithm. The full CSI scheme, also known as OPT algorithm [9] provides the lower-bound of the proposed scheme.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the performance of the proposed OPT-COV algorithm with the naive amplify-and-forward (NAF) algorithm [5], the pseudo match-and-forward (PMF) algorithm [5], SUB algorithm [9], the JMMSE-COV algorithm [15], OPT algorithm [9] and the suboptimal covariance (SUB-COV) algorithm. The full CSI scheme, also known as OPT algorithm [9] provides the lower-bound of the proposed scheme.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A relay precoding algorithm [4] and [5] for AF based multiple-input multiple-output (AF MIMO) relay has been developed to maximize the capacity of the source-destination link. In this algorithm, a precoding matrix is multiplied with the received signal at the relay for further signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…We also assume that the number of antennas at each node is , = 1, ⋅ ⋅ ⋅ , + 1, and the number of source symbols in each transmission is . Like [5], [6], [11]- [14], a linear nonregenerative relay matrix is used at each relay. The system block diagram is shown in Fig.…”
Section: System Modelmentioning
confidence: 99%
“…Note that the number of parallel channels that can be utilized is min{r, t}, i.e., the minimum number of parallel streams of the first-and second hop. In (9), it is shown that the strategy given by (6) is optimal if the relay mapping is constrained to be linear. However as we show, AF is in general suboptimal for the underlying channel.…”
Section: Linear Relayingmentioning
confidence: 99%
“…The work in (7; 8) investigates linear relay processing for the MIMO relay channel. In this paper, in contrast to (6)(7)(8)(9), we study an uncoded system, and we propose a nonlinear relaying scheme which is superior to linear relaying and performs close to the theoretical bound. Our proposed scheme is based on constellation permutation (10; 11) at the relay over different streams obtained by channel orthogonalization.…”
Section: Introductionmentioning
confidence: 99%